Catalyst‐free, Knoevenagel–Michael Addition Reaction of Dimedone under Microwave Irradiation: An Efficient One‐pot Synthesis of Polyhydroquinoline Derivatives. (24th June 2013) - Saha, M.; Luireingam, T. S.; Merry, T.; Pal, A. K.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>